Detection of BK virus by PCR in Suspected Graft Dysfunction in Renal Transplant Recipients and Cystitis in Bone Marrow Transplant Re (Pulse, 2025)
BK virus (BKV) is a prevalent infectious agent known to be a leading cause of nephropathy and graft loss among kidney transplant recipients. Furthermore, it has emerged as a significant concern for individuals undergoing hematopoietic stem cell transplantation, often presenting as hemorrhagic cystitis. However, the incidence of BK virus infection among transplant recipients in Bangladesh is unknown. Routine BKV PCR data were analyzed from hospital record from a total of 95 renal transplant recipients who were suspected of experiencing graft dysfunction, and 16 bone marrow transplants patients who developed cystitis and/or hematuria between October 2021 and December 2024. BKV was detected in 17 (17.89%) out of the 95 renal transplant recipients and in 11 (68.75%) of the 16 bone marrow transplant recipients. Co-infection with cytomegalovirus (CMV) was observed in 2 out of the 17 renal transplant recipients and in 5 out of the 11 bone marrow transplant recipients. Thus, prompt BKV identification by PCR may be important to decrease the likelihood of BKV associated nephropathy induced graft dysfunction and cystitis in bone marrow transplant.Pulse Volume 16, Issue 2 2024, P: 5-12